On the Primary Ionization Mechanism(s) in Matrix-Assisted Laser Desorption Ionization - Laura Molin; Roberta Seraglia; Zbigniew Czarnocki; Jan K. Maurin; Franciszek A. Pluciński; Pietro Traldi (Journal of Analytical Methods in Chemistry)
A mechanism is proposed for the first step of ionization occurring in matrix-assisted laser desorption ionization, leading to protonated and deprotonated matrix (Ma) molecules ([Ma+H]+ and [Ma-H]- ions). It is based on observation that in solid state, for carboxyl-containing MALDI matrices, the molecules form strong hydrogen bonds and their carboxylic groups can act as both donors and acceptors. This behavior leads to stable dimeric structures. The laser irradiation leads to the cleavage of these hydrogen bonds, and theoretical calculations show that both [Ma+H]+ and [Ma-H]- ions can be formed through a two-photon absorption process. Alternatively, by the absorption of one photon only, a heterodissociation of one of the O–H bonds can lead to a stable structure containing both cationic and anionic sites. This structure could be considered an intermediate that, through the absorption of a further photon, leads to the formation of matrix ions. Some experiments have been performed to evaluate the role of thermal ionization and indicate that its effect is negligible. Some differences have been observed for different matrices in the formation of analyte molecule (M) ion [M+H]+, [M-H]-, M+•, and [M-2H]-•, and they have been explained in terms of ionization energies, pKa values, and thermodynamic stability.